Immunodeficiency, Centromeric Instability, and Facial Dysmorphism (ICF) Syndrome: How HSCT alters the impairment of the DNA methylation process - Homa, Wojciech; Wanat, Joanna; Dzikowska, Izabela; Siejka, Agata; Stefaniak, Daria; Warunek, Aleksandra; Gronowicz, Gabriela; Chról, Michał; Zielińska, Weronika (Journal of Education, Health and Sport, 2025)
Introduction and purpose In 2024, the EBMT Inborn Errors Working Party published a study that confirmed the beneficial role of hematopoietic stem cell transplantation (HSCT) in patients with immunodeficiency, centromeric instability, and facial dysmorphism (ICF) syndrome. In this article, we aim to present the characteristics of ICF in an accessible way, including its genetic background, clinical presentation, immunological alterations, and treatment options. A brief description of the state of knowledge In recent years, published reviews and series of cases have expanded the range of known symptoms and complications occurring in patients with ICF. Our understanding of immunological alterations in ICF evolved from isolated defects of immunoglobulin production to a comprehensive model, which involves impairment of cellular immunity. Advances in molecular biology and genetics enabled insights into the DNA methylation machinery, which allowed us to gain a more precise understanding of the pathogenesis of ICF and also opened up opportunities for the development of new therapeutic options. Summary Inborn errors of immunity (IEI), such as ICF, are diagnosed at an early stage of life. It enables effective treatment with longer survival of the patients. It means that healthcare professionals are increasingly likely to encounter such patients in their clinical practice. Thus, it is crucial to inform about the usage of the HSCT in ICF syndrome and spread awareness of potential new treatment options, that may emerge in the near future.